Development Of A Nomogram To Guide The Monitoring Of Once Daily Dosing Gentamicin Regimen In Hospital Melaka - Sahak, Nursahjohana Md (2013)
The exact starting dose used in once daily dosing gentamicin (ODD) has not been clearly defined but it is typically equivalent to the sum of doses traditionally used with conventional dosing over a 24-hour period. However, most literatures have recommended a dosing range of 5 to 7 mg/kg/day. Despite these recommendations, anecdotal reports have shown that the usual dose used in ODD in Malaysia was much lower, with an average of 3.5 mg/kg. Therefore, clinical and bacteriological cures maybe different. Consequently, published monitoring method of ODD gentamicin in the literature may not be applicable in local setting. This study was carried out to evaluate the practice of ODD gentamicin, to determine its pharmacokinetic parameters and to develop a simple monitoring method applicable in Hospital Melaka.